Torque teno sus virus k2a (TTSuVk2a) in wild boars from northeastern Patagonia, Argentina - De Maio, Federico Andrés; Winter, Marina; Abate, Sergio; Birochio, Diego; Iglesias, Néstor Gabriel; Barrio, Daniel Alejandro; Bellusci, Carolina Paula (Springer Nature, 2024)
Torque teno sus virus k2a (TTSuVk2a) is a member of the family Anelloviridae that can establish persistent infections in both domestic pigs and wild boars. Its association with diseases has not been precisely elucidated, and it is often considered only as a commensal virus. This infectious agent has been reported in herds throughout the world. In this study, we investigated the detection rate and diversity of TTSuVk2a in free-living wild boars from northeastern Patagonia, Argentina. Total DNA was extracted from tonsil samples of 50 animals, nested PCR assays were carried out, and infection was verified in 60% of the cases. Sequence analysis of the viral non-coding region revealed distinct phylogenetic groups. These clusters showed contrasting patterns of spatial distribution, which presented statistically significant differences when evaluating spatial aggregation. In turn, the sequences were compared with those available in the database to find that the clusters were distinguished by having similarity with TTSuVk2a variants of different geographic origin. The results suggested that Patagonian wild boar populations are bearers of diverse viral strains of Asian, European, and South American provenance.
Keywords: Ciencias naturales::Ciencias biológicas::Biología celular, Microbiología